FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Fernandes, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to obtain empirical evidence on the effect of firm size, profitability, and leverage of companies on firm value in manufacturing companies listed in Indonesia Stock Exchange in the period 2015-2017. Research samples are 67 companies out of 143 companies data using purposive sampling method. Results of this research obtained the firm size have no effect to firm value, profitability have positive effect to firm value, and leverage have no effect to firm value.